Hip strength ratios and lower extremity injury in NCAA Division I soccer players - Miller, M. M.; Hertel, J.; Van Lunen, B.; Cortes, N.; Schroeder, M.; Grooms, D.; Onate, J. (Journal of Athletic Training, 2012)
Context: Weak hip musculature has been identified as a factor in lower extremity injury; however, not all individuals exhibiting muscle weakness experience injury. Objective: The purpose of this study was to examine strength ratios of the hip musculature between college soccer players who did and did not suffer lower extremity injuries. Design: Cohort study. Settings: Movement analysis laboratory. Participants: 382 NCAA Division I collegiate soccer players; 200 male (179.6 ± 6.7 cm, 76.6 ± 7.8 kg, 19.5 ± 1.3 years) and 182 female (167.4 ± 6.0 cm, 62.7 ± 7.1 kg, 19.3 ± 1.1 years). Interventions: Peak isometric hip and knee strength was measured prospectively using a portable load cell (BTE Technologies, Hanover, MD). Frontal and sagittal plane motions were measured in the standing position; transverse plane rotations were measured in the seated position. Peak isometric knee strength was measured in the seated position. Peak strength values were arranged into four strength ratios: hip flexion:extension (FLX:EXT), abduction:adduction (ABD:ADD), external:internal rotation (ER:IR), knee extension:flexion (EXT:FLX). Ratio values were obtained by dividing peak strength of the agonist muscle by peak strength of the antagonist. Main Outcome Measures: Athletes were followed prospectively for two consecutive seasons. Each team`s ATC recorded all injuries. Athletes were then classified as either "injured" (n=136) or "non-injured" (n=178) for the purpose of this analysis. Lower extremity injury was defined as any event affecting the lower limb, originating at the hip and extending distally, that caused participation time loss for one or more days. Independent samples t-tests were conducted, with an a priori alpha level of 0.05, in order to determine if differences in strength ratio asymmetries were present between athletes who did and did not sustain a lower extremity injury. Results: A significant difference in strength ratios, with respect to lower extremity injury, was reported for one of the four calculated strength ratios: (Hip FLX:EXT p=.026, Hip ABD:ADD p=.270, Hip ER:IR p=.893, Knee EXT:FLX p=.154). Average (mean ± sd) strength ratios were: Hip FLX:EXT injured (117.9 ± 43.9%) and non-injured (108.8 ± 28.2%); Hip ABD:ADD injured (84.3 ± 36.0%) and non-injured (80.5 ± 23.4%); Hip ER:IR injured (109.7 ± 28.6%) and non-injured (110.1 ± 30.9%); Knee EXT:FLX injured (93.8 ± 30.7%) and non-injured (98.6 ± 28.5%).